Therapeutic significance of vitamin D and calcium in reducing the risk of preeclampsia - E. N. Vasilyeva; L. I. Maltseva; T. G. Denisova; L. I. Gerasimova (IRBIS LLC, 2019)
Aim: to study the possibility of reducing the incidence of preeclampsia (PE) by giving vitamin D and calcium (Ca) to pregnant women with a high PE risk starting from the second trimester of pregnancy.Materials and methods. A total of 101 patients from the PE high risk group were examined on weeks 14-16 of pregnancy followed by treatment with vitamin D and Ca; then, the course of pregnancy and labor was analyzed. Serum 25-hydroxycholecalciferol, vitamin D binding protein, endothelin 1-38, and ionized Ca were determined using enzyme immunoassays.Results. In the examined women at high risk of PE, severe serum deficiency of vitamin D and Ca was detected. In patients treated with vitamin D and Ca, a two-fold decrease in the incidence of PE, a three-fold decrease in the incidence of intrauterine growth retardation syndrome, and a decrease in the number of urgent surgery-assisted deliveries were found.Conclusion. Therapy with vitamin D and Ca from the second trimester of pregnancy increases the availability of vitamin D, leads to a more favorable course of pregnancy, and prevents the development of severe forms and early onset of PE in patients at high risk.